2006
DOI: 10.1038/sj.leu.2404483
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the proapoptotic BH3-only protein BIM by glucocorticoids, survival signals and proteasome in chronic lymphocytic leukemia cells

Abstract: Glucocorticoids induce apoptosis in chronic lymphocytic leukemia (CLL) cells through a caspase-dependent mechanism. However, their mechanism of action remains unknown. We have studied the regulation of the proapoptotic BH3-only Bcl-2 interacting mediator of cell death (BIM) in CLL cells. We demonstrate that glucocorticoids upregulate BIM at protein and mRNA levels. We have investigated the ability of different survival signals, such as 12-O-tetradecanoylphorbol 13-acetate (TPA), stromal cell-derived factor-1a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 53 publications
2
35
1
Order By: Relevance
“…44,45 In addition, the Constitutive activation of Syk in B-CLL S Gobessi et al treatment of CLL cells with R406 decreased the basal activity of several downstream signaling molecules that play important roles in regulating CLL-cell survival, such as the Akt, ERK and GSK-3 kinases and the FoxO1/3a transcription factors. 25,26,37,46,47 The specificity of R406 in inhibiting Syk-mediated activation of Akt and ERK was further confirmed in experiments with a constitutively active TEL-Syk protein.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…44,45 In addition, the Constitutive activation of Syk in B-CLL S Gobessi et al treatment of CLL cells with R406 decreased the basal activity of several downstream signaling molecules that play important roles in regulating CLL-cell survival, such as the Akt, ERK and GSK-3 kinases and the FoxO1/3a transcription factors. 25,26,37,46,47 The specificity of R406 in inhibiting Syk-mediated activation of Akt and ERK was further confirmed in experiments with a constitutively active TEL-Syk protein.…”
Section: Discussionmentioning
confidence: 69%
“…These pathways can be activated in CLL B cells by BCR stimulation and have been shown to increase the survival of the leukemic cells in vitro. 25,26,[37][38][39][40] As shown in Figure 4a, short treatment of CLL B cells with increasing concentrations of R406 resulted in a dose-dependent reduction in basal Akt phosphorylation and induced a more prominent reduction in the phosphorylation of glycogen synthase kinase (GSK)-3 and FoxO1/3a, both of which are direct substrates of Akt. In addition, R406 reduced the phosphorylation of ERK in those cases where the basal phosphorylation of this kinase could be detected.…”
Section: Inhibition Of Syk By R406 Reduces the Basal Activity Of The mentioning
confidence: 99%
“…25,26 Homozigous deletion of Bim is associated with mantle cell lymphoma 27 and survival of autoreactive T and B cells, 28,29 and repression of Bim expression by EBV has a significant role in Burkitt lymphoma. 30 Several antitumor chemotherapies were demonstrated to kill neoplastic cells through Bim-activated pathways, including a Raf kinase inhibitor in acute myeloid cells, 31 glucocorticoids in leukaemia cell lines and primary leukemia cells, 32,33 ABT-737 for chronic lymphocytic leukaemia cells and myeloma cell lines 18 and paclitaxel in xenografts of epithelial cancer cells. 34 Altogether, Bim can be classified as a powerful tumour suppressor, and its strong pro-apoptotic activity is regulated both at transcriptional and post-translational levels.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Iglesias-Serret et al 37 published that Bim is essential for glucocorticoid-induced apoptosis in CLL and upregulated at the transcriptional level. Longo et al 38 reported that Bim levels varied between CLL samples, however no further explanation was given for this observation.…”
Section: Discussionmentioning
confidence: 99%